Say you say me: on entrepreneurship education as a differentiation strategy - Abu Samah, Ainon Jauhariah; Omar, Azura (World Business Institute, 2011)
This study is built around a Malaysian private university’s quest to differentiate itself using entrepreneurship education in the nation’s competitive higher education industry. Students’ views on Bachelor of Business Administration and Bachelor of Management (Entrepreneurship) are drawn through personal interviews and focus group to answer two main questions; how does entrepreneurship education differ from business education? And how can the university improve its entrepreneurship education? The research uncovered four basic points in which the university’s two programs part ways that is in terms of program content, mode of delivery, lecturers and program outcome. The students interviewed generally perceive Bachelor of Business Management (Entrepreneurship) as a specialized program meant to create business founders whereas Bachelor of Business Administration is seen as a mould for industry-ready worker.